Reuben Cleary book manuscripts - Cleary, Reuben, 1835-1898.
Two volume manuscript entitled Brazil under the monarchy; a record of facts and observations from notes taken in Brazil during a period of more than twenty years. A revised and expanded version of the manuscript (4 volumes) is entitled Chronicas Lageanas. Includes observations made by Cleary while practicing medicine in Brazil between 1865 and 1885. Subjects include customs, the role of foreigners, government, history, medicine, society, religion, new technologies including the telephone, and transportation.
Microfilm edition of Brazil under the monarchy available
Microfilm edition of Chronicas Lageanas available
Microfilm produced from originals in the Manuscript Division.
Confederate expatriate and physician.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aliens -- Brazil; Medicine -- Practice -- Brazil; Medicine -- Brazil; Technology -- Brazil; Telephone -- Brazil; Transportation -- Brazil; Brazil -- History; Brazil -- Politics and government -- 1822-1889.; Brazil -- Religion; Brazil -- Social life and customs; Expatriates, Confederate; Physicians